Influence of processing on the quality of pomaceas juice (Pyrus communis and Malus domestica) - Rocha, Andressa Schaia; Zielinski, Acácio Antonio Ferreira; Ávila, Suelen; Nogueira, Alessandro; Wosiacki, Gilvan (My University, 2013)
Pear (Pyrus communis), which is intensively cultivated in subtropical and temperate climates, has recently attained the 3rd position in the world fruit ranking, just after apple and peach. This fruit exhibits certain similarities to apple with respect to the pulp, but pear is used as a raw material only when apple is no longer available, which suggests that the same technology line may be utilized. Both fruits do have processing compatibilities, and it is permissible to add pear juice to apple juice at levels defined by law. Quality indicators, such as pH, total acidity, total phenolic compounds and antioxidant activity were used. The simple sugar analysis clearly defines fructose as the main component in pear juice, and lower figures were found when enzymatic processing was used. Color intensity measured instrumentally was much greater in pear juice with all processing methods and in apple juice when an enzymatic method was used. The results clearly indicate proper ways of processing pear and apple, aiming to have better products, as the grinding and extraction processing steps surely affect the fruit juice quality.

A pera (Pyrus communis), terceira fruta cultivada em climas temperados e subtropicais e somente superada pela maçã e o pêssego, guardam semelhanças físicas e químicas enquanto pomaceas. Somente há processamento de pera na falta de maçã enquanto matéria prima, o que sugere que a mesma linha tecnológica possa ser usada. São compatíveis, sendo permitida a adição de suco de pera no suco de maçã pela legislação. Os indicadores de qualidade mais acentuados no suco de pera foram acidez, o teor de compostos fenólicos totais e a capacidade antioxidante. Na distribuição de açúcares os teores de frutose foram expressivamente mais acentuados no suco de pera, com menores valores quando era empregado o método enzimático. A intensidade de cor, determinada instrumentalmente, foi mais expressiva no suco de pera, em especial no despolpamento, enquanto que no de maçã, no enzimático. Os resultados indicam de forma clara que a pera se comporta como matéria-prima aos processos com aptidão ao processamento de maçã, todavia cada fruta tem o seu próprio perfil de qualidade. Os resultados claramente apontam para os procedimentos mais adequados para obter bons produtos eis que as etapas de moagem e a de extração seguramente contribuem para a modificação da qualidade dos sucos de pera e de maçã.
Influência do processamento na qualidade do suco de pomáceas (Pyrus communis e Malus domestica)
Keywords: Juice processing; Apple; Pear; Quality profile